The amino acid response to a mixed meal in patients with type 2 diabetes: effect of sitagliptin treatment. Issue 11 (4th August 2014) - Muscelli, E.; Frascerra, S.; Casolaro, A.; Baldi, S.; Mari, A.; Gall, W.; Cobb, J.; Ferrannini, E.
<x xml:space="preserve">Abstract</x> Aims Amino acid (AA) metabolism is altered in type 2 diabetes (T2D), and fasting levels of α‐hydroxybutyrate (α‐HB), a biomarker for insulin resistance, have been suggested to track AA metabolism. We investigated the changes in AA and α‐HB induced by a mixed‐meal tolerance test (MTT) and the effects of sitagliptin treatment. Methods Forty‐seven T2D patients [56 ± 7 years, body mass index (BMI) 29.9 ± 4.2 kg/m2] were randomized to sitagliptin (100 mg/day, 6 weeks) or placebo. Seven age‐ and BMI‐matched non‐diabetic subjects served as control (CT). Results During a 5‐h MTT, branched‐chain AA (BCAA) peaked earlier in T2D than CT [75(25) vs. 62(3) mmol/l·h over 2 h, median(interquartile range), p = 0.05], and rose higher [5‐h increment: 31(23) vs. 19(24) mmol/l·h, p = 0.05]. Fasting α‐HB was higher [7.5(2.7) vs. 5.9(1.3) µg/ml, p = 0.04 T2D vs. CT], and its meal‐induced increments were larger [24(99) vs. −41(86) µg/ml·h, p = 0.006]. Plasma non‐esterified fatty acids (NEFA) declined during MTT, but their increments were greater in patients (53 ± 16 vs. 35 ± 10 mEq/l·h, p = 0.005). Compared to placebo, both BCAA [−6.4(21.1) vs. 0.0(48.0) mmol/l·h, p = 0.01] and α‐HB increments [−114(250) vs. 114(428) µg/ml·h, p = 0.002] decreased with sitagliptin, and meal‐induced NEFA suppression was improved. Changes in BCAA and α‐HB were reciprocally related to changes in insulin sensitivity (ρ = −0.37 and −0.43, p ≤ 0.01). Conclusions T2D is associated with a hyperaminoacidaemic response to MTT, which circulating α‐HB levels track. Sitagliptin‐induced glycaemic improvement was associated with reductions in BCAA and α‐HB excursions and better NEFA suppression, in parallel with improved insulin sensitivity, confirming that α‐HB is a readout of metabolic overload.